Crude protein reduction with amino acid supplementation in tambaqui fingerling diets - Charlyan de Sousa Lima; Marcos Antonio Delmondes Bomfim; Jefferson Costa de Siqueira; Eduardo Arruda Teixeira Lanna; Felipe Barbosa Ribeiro; Danielli dos Santos Firmo (Semina: Ciências Agrárias, 2015)
The aim of this study was to evaluate the effect that reduced crude protein (CP) diets with amino acid  supplementation, based on the ideal protein concept, have on the performance of tambaqui fingerlings. In total, 750 fingerlings with an initial weight of 0.44 ± 0.14 g, were used in a completely randomized design, with six treatments, five replications, and 25 fish per experimental unit. Treatments consisted of six isocaloric, isocalcic, isophosphoric, and isolysinic diets containing 32.0, 30.5, 29.0, 27.5, 26.0, and 24.5% CP. Performance parameters, carcass yield, body composition (body humidity, protein, and fat content), and nitrogen retention efficiency (NRE) of the fish were evaluated. When the CP content was reduced to 27.5%, there was an improvement in weight gain, specific growth rate, feed conversion, and protein efficiency rate. Feed intake was higher in fish fed diets containing 26% CP, followed by those fed diets containing 29 and 27.5% CP; diets containing other levels of CP did not differ among themselves. CP intake was reduced by the use of diets containing 24% CP, and the carcass yield was not influenced by the treatments. Reduced CP had no influence on body composition. NRE was higher in response to diets containing 26.0 and 24.5% CP. Reducing dietary CP content, from 32.0 to 24.5%, based on the ideal protein concept, is possible for tambaqui fingerlings, and a decrease of up to 24.5% enhances the fish performance.